Mechanics 2 : Advanced level mathematics - Quadling, Douglas (Cambridge : New York : Singapore : Cambridge university press, 2005)
Mechanics 2 corresponds to unit M2. It covers motion of a projectile, equilibrium of a rigid body, uniform motion in a circle, Hooke's law and linear motion under a variable force.
Keywords: Mechanics -- Mathematics; Mechanics -- Problems, exercises, etc. -- Mathematics